Sequential Broadening of CTL Responses in Early HIV-1 Infection Is Associated with Viral Escape - Karlsson, A; Iversen, A; Chapman, J; de Oliveira, T; Spotts, G; Mcmichael, A; Davenport, M; Hecht, F; Nixon, D (Public Library of Science, 2007)
Background. Antigen-specific CTL responses are thought to play a central role in containment of HIV-1 infection, but no consistent correlation has been found between the magnitude and/or breadth of response and viral load changes during disease progression. Methods and Findings. We undertook a detailed investigation of longitudinal CTL responses and HIV-1 evolution beginning with primary infection in 11 untreated HLA-A2 positive individuals. A subset of patients developed broad responses, which selected for consensus B epitope variants in Gag, Pol, and Nef, suggesting CTL-induced adaptation of HIV-1 at the population level. The patients who developed viral escape mutations and broad autologous CTL responses over time had a significantly higher increase in viral load during the first year of infection compared to those who did not develop viral escape mutations. Conclusions. A continuous dynamic development of CTL responses was associated with viral escape from temporarily effective immune responses. Our results suggest that broad CTL responses often represent footprints left by viral CTL escape rather than effective immune control, and help explain earlier findings that fail to show an association between breadth of CTL responses and viral load. Our results also demonstrate that CTL pressures help to maintain certain elements of consensus viral sequence, which likely represent viral escape from common HLA-restricted CTL responses. The ability of HIV to evolve to escape CTL responses restricted by a common HLA type highlights the challenges posed to development of an effective CTL-based vaccine. © 2007 Karlsson et al.